Indoor Air Quality Monitoring through Internet of Things System: A Case Study at UTHM-Fraunhofer IEM Innovation Lab - RAVI, SHASHWAR KUMAR; ABD RAHMAN , RAMHUZAINI (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Indoor air quality (IAQ) significantly influences occupant health, comfort, and productivity, particularly in high-occupancy academic environments. This study develops an Internet of Things (IoT)-based system for real-time IAQ monitoring at Room G1 035B, UTHM-Fraunhofer IEM Innovation Lab, addressing limitations of traditional offline monitoring methods. The objectives are to investigate the interplay between IAQ, IoT technology, and mechanical ventilation and air conditioning (MVAC) systems; design a functional real-time IAQ monitoring system; and assess IAQ conditions in the selected laboratory. The system, utilizing an ESP32 microcontroller with DHT22, SGP30, and GP2Y1010AU0F sensors, was programmed via Arduino IDE and integrated with the ThingSpeak cloud platform for data storage and visualization. Data was collected over five days (June 28 to July 2, 2025), comparing ventilated weekdays and non-ventilated weekends. Results demonstrated the system’s ability to detect environmental fluctuations, with MVAC operations influencing pollutant levels and revealing energy inefficiencies due to overcooling. The system offers a scalable, cost-effective solution for real-time IAQ monitoring, providing actionable insights for healthier indoor environments.